Magnetic porous carbon-coated cyclodextrin / epichlorohydrin copolymer capable of rapidly adsorbing polychlorinated biphenyl as well as preparation method and application of magnetic porous carbon-coated cyclodextrin / epichlorohydrin copolymer
Through the combination of magnetic porous carbon @ cyclodextrin/epchlorohydrin copolymer, the problems of long adsorption time, poor selectivity and unrecyclable of existing PCB adsorption materials are solved, and fast and efficient PCB is achieved Biphenyl adsorption and removal effects.
Patent Information
- Application Number
- CN202411285276.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The existing PCB adsorbent materials have problems such as long adsorption time, poor selectivity, low adsorption capacity and unrecyclable, and it is difficult to meet the demand for PCB removal in environmental soil and wastewater.
Magnetic porous carbon @ cyclodextrin/epoxychlorohydrin copolymer is used to form an insoluble polymer by magnetically functionalizing the combination of porous carbon materials and cyclodextrins, achieving rapid adsorption and reusability.
It has achieved the effect of fast adsorption rate, good selectivity, high adsorption capacity and reusable reuse, and has efficient removal of PCBs in soil and water samples, short adsorption time and strong reusability.
Smart Images

Figure CN119140070A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer capable of rapidly adsorbing polychlorinated biphenyls, and a preparation method and application thereof. Background Art
[0002] Polychlorinated biphenyls (PCBs) are chlorine-substituted biphenyls, with 209 homologues. They have excellent acid and alkali resistance, heat resistance, electrical insulation and other characteristics. They have been widely used in the power industry, printing and plastic processing and other fields. However, due to the high toxicity, carcinogenicity, long-term stability and bioaccumulation of PCBs, they pose a serious threat to human health and ecological security. Therefore, the detection and removal of PCBs has become a research hotspot for scientific researchers in recent years.
[0003] At present, the treatment methods for removing PCBs from soil or wastewater include physical adsorption, chemical treatment and biodegradation. Among them, physical adsorption is favored because of its advantages such as simple operation, high efficiency, economy and practicality. The key to the adsorption method lies in the selection of adsorbents. In recent years, there have been many research reports on PCB adsorption materials, but most of the reported adsorption materials have problems such as long adsorption time, poor adsorption selectivity, low adsorption capacity and non-recyclability, which are difficult to meet the requirements of practical applications. In response to these problems, the development of new adsorption materials with good adsorption selectivity, high adsorption efficiency and reusability is of great significance for the treatment of PCBs in environmental soil and wastewater.
[0004] Porous carbon has rich pore structure, large specific surface area, strong adsorption capacity and good chemical stability, and is widely used as an adsorbent to remove various pollutants. However, conventional porous carbon materials have shortcomings in practical applications, such as difficulty in separation and recycling, and easy to produce secondary pollution. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer for rapid adsorption of polychlorinated biphenyls, and a preparation method and application thereof. The obtained magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer of polychlorinated biphenyls has the advantages of fast adsorption rate, good selectivity, high adsorption capacity and reusability, and can be used to simultaneously adsorb 8 types of polychlorinated biphenyls in soil and water samples.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer for rapid adsorption of polychlorinated biphenyls, comprising the following steps:
[0008] S1. The unsaturated polyester resin is mixed with potassium hydroxide after a first calcination, and then ground and calcined for a second time to obtain a porous carbon material;
[0009] S2. The porous carbon material is mixed with deionized water and ultrasonically dispersed, and then ferrous chloride tetrahydrate and ferric chloride hexahydrate are added and stirred to dissolve; after dissolution, nitrogen oxygen removal, heating, pH adjustment, constant temperature reaction, cooling, solid-liquid separation, and washing are sequentially performed to obtain a magnetic porous carbon material;
[0010] S3. After a first mixing of cyclodextrin, sodium borohydride and double distilled water, a magnetic porous carbon material is added for a second mixing; then epichlorohydrin is added dropwise and a first stirring reaction is carried out; after the reaction is completed, the pH is adjusted, and then a second stirring reaction is carried out; after the reaction is completed, paraffin oil and Span / Tween compound emulsifier are added, and a third stirring reaction is carried out; after the reaction is completed, a mixed solution of water and acetone is added, and then the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer is obtained by filtering, washing and drying.
[0011] In the present invention, the porous carbon material is magnetically functionalized, so that the contaminated adsorbent can be easily separated, thereby achieving the purpose of separation, purification and reuse. Moreover, there is a hydrophobic inner cavity and a hydrophilic outer edge in the molecular structure of cyclodextrin. Its hydrophobic inner cavity can form inclusion complexes with organic pollutants through "host-guest", which is beneficial to the effective adsorption of pollutants. However, cyclodextrin is easily soluble in water, which makes it difficult to recycle the inclusion complex constructed after adsorbing organic pollutants from aqueous solutions, limiting its application. In order to solve the problem of water solubility of cyclodextrin, the present invention forms an insoluble polymer by polymerizing it with an organic crosslinking agent, which can adsorb and remove organic pollutants from aqueous solutions.
[0012] Preferably, the mass ratio of the calcined unsaturated polyester resin to potassium hydroxide in S1 is 1-10:1-10.
[0013] Preferably, in S1, the first calcination temperature is 200-400° C., and the calcination time is 1-3 h; the second calcination temperature is 600-1000° C., and the calcination time is 1-3 h.
[0014] Preferably, the volume mass ratio of the porous carbon material, double distilled water, ferrous chloride tetrahydrate and ferric chloride hexahydrate in S2 is 0.2-0.5 g: 150-500 mL: 1-8 g: 5-15 g.
[0015] Preferably, the nitrogen ventilation and oxygen removal time in S2 is 10-30 minutes.
[0016] Preferably, the heating temperature in S2 is 50-90°C.
[0017] Preferably, in said step S2, the pH value is adjusted to 9-13, and the pH adjusting agent is 25% ammonia water.
[0018] Preferably, the constant temperature reaction time in S2 is 1 to 15 hours.
[0019] Preferably, the solid-liquid separation in S2 is performed by magnetic separation.
[0020] Preferably, the washing in S2 is carried out with double distilled water.
[0021] Preferably, the volume mass ratio of cyclodextrin, sodium borohydride, double distilled water, magnetic porous carbon material, epichlorohydrin, paraffin oil, Span / Tween compound emulsifier, water and acetone in S3 is: 0.5-5g: 2-50mg: 15-30mL: 2-4g: 1-10mL: 30-80mL: 5-40mL: 10-20mL: 10-20mL.
[0022] Preferably, the volume ratio of the Span / Tween compound emulsifier is 1-10:1-10; the cyclodextrin is any one of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin; the Span is any one of Span-20, Span-40, and Span-80.
[0023] Preferably, the first mixing in S3 is performed by heating the mixture in a water bath to 30-50° C. and stirring the mixture into a paddle shape at a stirring speed of 200 r / min; and the second mixing time is 10-20 min.
[0024] Preferably, the pH value in S3 is adjusted to 9-13, and the pH adjuster is 0.1 mol / L sodium hydroxide solution.
[0025] Preferably, the stirring time of the first stirring reaction in S3 is 5 to 30 minutes; the stirring time of the second stirring reaction is 5 to 60 minutes; and the stirring time of the third stirring reaction is 2 to 36 hours.
[0026] In a second aspect, the present invention provides a magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer for rapid adsorption of polychlorinated biphenyls, which is prepared by the above-mentioned preparation method.
[0027] In a third aspect, the present invention provides the use of the above-mentioned magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer in the adsorption of polychlorinated biphenyl pollutants, wherein the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer adsorbs polychlorinated biphenyls in soil and water samples.
[0028] Contains at least the following beneficial technical effects:
[0029] (1) The adsorbent provided by the present invention has short adsorption time, good selectivity, high adsorption capacity and recyclability, and can be used to simultaneously and rapidly adsorb multiple polychlorinated biphenyls in soil and water samples.
[0030] (2) The present invention uses waste unsaturated polyester resin particles with uniform morphology as a carbon source, and prepares porous carbon nanoparticles with multi-pores and uniform morphology through high-temperature calcination combined with potassium hydroxide activation technology. The composite material constructed based on this porous carbon has a significant advantage in improving the adsorption rate. The porous carbon is further magnetically functionalized through a one-pot method to obtain a magnetic porous carbon material, which can achieve rapid solid-liquid separation, thereby achieving the purpose of reuse.
[0031] (3) The cyclodextrin of the present invention can form inclusion complexes with hydrophobic polychlorinated biphenyls, showing strong recognition performance for polychlorinated biphenyls, which helps to improve the adsorption capacity. Therefore, the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer composite material synthesized with cyclodextrin as a functional monomer has the characteristics of fast adsorption rate, good selectivity and reusability for polychlorinated biphenyls.
[0032] (4) The adsorbent described in the present invention has a good adsorption effect on various polychlorinated biphenyls, and can reach adsorption equilibrium within 5 minutes. The adsorption amount is 80-97 μg / g. After repeated adsorption for 5 times, the adsorption capacity is still maintained at more than 80% of the initial value. The adsorption removal rate of polychlorinated biphenyls in soil and water samples is as high as more than 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Scanning electron micrographs of different materials, where: (a) is unsaturated polyester resin, (b) is porous carbon, (c) is magnetic porous carbon, and (d) is magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer;
[0034] Figure 2 Infrared images of magnetic porous carbon, β-cyclodextrin and magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer;
[0035] Figure 3 This is a graph showing the effect of adsorption time on the adsorption of polychlorinated biphenyls by magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0037] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0038] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the main idea or essential features of the present invention. Therefore, from all points of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any reference numerals in the claims should not be regarded as limiting the claims involved.
[0039] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.
[0040] It should also be understood that the specific embodiments described above are only used to explain the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, which should be covered by the protection scope of the present invention / invention.
[0041] Example 1
[0042] This embodiment provides a method for preparing a magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer for rapid adsorption of polychlorinated biphenyls:
[0043] S1. Take unsaturated polyester resin in a porcelain crucible, place it in a muffle furnace and calcine it at 400°C for 2h to obtain an initial product. The initial product is mixed with potassium hydroxide in a mass ratio of 1:1, ground into powder, and placed in a tube furnace. Under nitrogen protection, calcine at 800°C for 2h to obtain a porous carbon material.
[0044] S2. Take 0.35g of porous carbon material and put it in 350mL of double distilled water for ultrasonic dispersion for 30 minutes. Add 4g of ferrous chloride tetrahydrate and 10.9g of ferric chloride hexahydrate, stir magnetically to dissolve, and then pass nitrogen to remove oxygen for 20 minutes. Heat the solution to 70°C, add 25% ammonia water to adjust the pH value of the solution to close to 11, react at a constant temperature for 6 hours, and then cool to room temperature. Use a magnet to separate the solid and liquid to collect the solid product, wash it with double distilled water for many times, and vacuum dry it at 60°C for 12 hours to obtain a magnetic porous carbon material.
[0045] S3. Take 2g of β-cyclodextrin, 8mg of sodium borohydride and 20mL of double distilled water in a three-necked round-bottom flask, stir the mixture into a paddle shape at a stirring speed of 200r / min in a 35°C water bath, then add 3g of magnetic porous carbon, stir for 15min, then add 2.97mL of epichlorohydrin to the round-bottom flask at a rate of 2-3 drops per second, continue stirring and reacting for 15min after the addition is complete, then slowly add 0.1mol / L sodium hydroxide solution to the round-bottom flask until the pH value of the reaction solution is close to 7.0. Continue stirring and reacting for 15min after the addition is complete, finally add 44mL of paraffin oil and 20mL of Span-80 / Tween-80 composite emulsifier (volume ratio 3:1), adjust the stirring speed to 500r / min, and react for 18h. After the reaction was completed, 30 mL of a mixed solution of water and acetone (volume ratio 1:1) was added, the product was collected by filtration, washed 5 times with ethanol and water respectively, and then placed at 60°C for vacuum drying for 12 h to obtain a magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer composite material.
[0046] Example 2
[0047] This embodiment provides a method for preparing a magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer for rapid adsorption of polychlorinated biphenyls:
[0048] S1. Take unsaturated polyester resin in a porcelain crucible, place it in a muffle furnace and calcine it at 200°C for 1 hour to obtain an initial product. The initial product is mixed with potassium hydroxide in a mass ratio of 2:5, ground into powder, and placed in a tube furnace. Under nitrogen protection, calcine at 600°C for 1 hour to obtain a porous carbon material.
[0049] S2. Take 0.2g of porous carbon material and put it in 150mL of double distilled water for ultrasonic dispersion for 30min, add 1g of ferrous chloride tetrahydrate and 5g of ferric chloride hexahydrate, stir magnetically to dissolve, and then pass nitrogen to remove oxygen for 10min, heat the solution to 50°C, add 25% ammonia water to adjust the pH value of the solution to close to 9, react at a constant temperature for 2h, and then cool to room temperature, use a magnet to separate the solid and liquid to collect the solid product, wash it with double distilled water several times, and vacuum dry it at 60°C for 12h to obtain a magnetic porous carbon material.
[0050] S3. Take 0.5g of β-cyclodextrin, 2mg of sodium borohydride and 15mL of double distilled water in a three-necked round-bottom flask, stir the mixture into a paddle shape at a stirring speed of 200r / min in a 35°C water bath, then add 2g of magnetic porous carbon, stir for 10min, then add 1mL of epichlorohydrin to the round-bottom flask at a rate of 2-3 drops per second, continue stirring and reacting for 5min after the addition is complete, then slowly add 0.1mol / L sodium hydroxide solution to the round-bottom flask until the pH value of the reaction solution is close to 6.0. Continue stirring and reacting for 5min after the addition is complete, finally add 30mL of paraffin oil and 5mL of Span-80 / Tween-80 composite emulsifier (volume ratio 3:1), adjust the stirring speed to 500r / min, and react for 4h. After the reaction was completed, 20 mL of a mixed solution of water and acetone (volume ratio 1:1) was added, the product was collected by filtration, washed 5 times with ethanol and water respectively, and then placed at 60°C for vacuum drying for 12 h to obtain a magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer composite material.
[0051] Example 3
[0052] This embodiment provides a method for preparing a magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer for rapid adsorption of polychlorinated biphenyls:
[0053] S1. Take unsaturated polyester resin in a porcelain crucible, place it in a muffle furnace and calcine it at 300°C for 3 hours to obtain an initial product. The initial product is mixed with potassium hydroxide in a mass ratio of 5:2, ground into powder, and placed in a tube furnace. It is calcined at 1000°C for 3 hours under nitrogen protection to obtain a porous carbon material.
[0054] S2. Take 0.5g of porous carbon material and put it in 500mL of double distilled water for ultrasonic dispersion for 30 minutes. Add 8g of ferrous chloride tetrahydrate and 15g of ferric chloride hexahydrate, stir magnetically to dissolve, and then pass nitrogen to remove oxygen for 30 minutes. Heat the solution to 90°C, add 25% ammonia water to adjust the pH value of the solution to close to 13, react at a constant temperature for 15 hours, and then cool to room temperature. Use a magnet to separate the solid and liquid to collect the solid product, wash it with double distilled water for many times, and vacuum dry it at 60°C for 12 hours to obtain a magnetic porous carbon material.
[0055] S3. Take 5g of β-cyclodextrin, 50mg of sodium borohydride and 30mL of double distilled water in a three-necked round-bottom flask, stir the mixture into a paddle shape at a stirring speed of 200r / min in a 50℃ water bath, then add 4g of magnetic porous carbon, stir for 20min, then add 10mL of epichlorohydrin to the round-bottom flask at a rate of 2-3 drops per second, continue stirring and reacting for 30min after the addition is complete, then slowly add 0.1mol / L sodium hydroxide solution to the round-bottom flask until the pH value of the reaction solution is close to 10.0. Continue stirring and reacting for 60min after the addition is complete, finally add 80mL of paraffin oil and 40mL of Span-80 / Tween-80 composite emulsifier (volume ratio 3:1), adjust the stirring speed to 500r / min, and react for 36h. After the reaction was completed, 40 mL of a mixed solution of water and acetone (volume ratio 1:1) was added, the product was collected by filtration, washed with ethanol and water for 5 times respectively, and then placed at 60°C for vacuum drying for 12 h to obtain a magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer composite material.
[0056] Experimental Example 1
[0057] The magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer prepared in Example 1 was characterized:
[0058] 1. Scanning Electron Microscope Characterization
[0059] The unsaturated polyester resin and the porous carbon material, magnetic porous carbon and magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer prepared in Example 1 were characterized by scanning electron microscopy. The characterization results are shown in the attached Figure 1 .from Figure 1 (a) It can be observed that the unsaturated polyester resin is composed of a large number of nanoparticles, and the particle size distribution of these particles is 10-20nm. The porous carbon obtained by mixing the unsaturated polyester resin with potassium hydroxide and carbonizing it at high temperature ( Figure 1 b) The particle size does not change much, but the particle surface becomes rough and fluffy, and there are a lot of pores between these particles. Figure 1 c), the particle size of the magnetic porous carbon particles increases, and slight agglomeration occurs. Magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer ( Figure 1 The particle size of the nanoparticles in d) is relatively large, a polymer film can be observed on the surface of the particles, and there are a large number of pores between the particles. This porous structure is conducive to improving the surface area utilization of the composite material, thereby improving its adsorption performance.
[0060] 2. Infrared spectroscopy characterization
[0061] The β-cyclodextrin, the magnetic porous carbon prepared in Example 1, and the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer were characterized by infrared spectroscopy. Figure 2The infrared spectrum of magnetic porous carbon is shown at 3425 cm -1 The broad peak at 1640cm is the OH stretching vibration absorption peak; -1 The peak at 583cm corresponds to the stretching vibration absorption peak of C=O; -1 The absorption peak at is attributed to the characteristic peak of Fe-O stretching vibration. The characteristic peak of β-cyclodextrin infrared spectrum is 3425cm -1 (OH stretching vibration), 2930 cm -1 and 2860cm -1 (CH asymmetric and symmetric stretching vibration absorption peaks, respectively), 1640cm -1 (HOH bending deformation), 1420cm -1 (-CH2 in-plane bending vibration), 1156cm -1 (COC stretching vibration) and 1030cm -1 (CO stretching vibration). The infrared spectrum of the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer has characteristic absorption peaks of both magnetic porous carbon and β-cyclodextrin, from which it can be judged that the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer adsorbent is synthesized.
[0062] 3. Dynamic adsorption performance study
[0063] 30 mg of the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer adsorbent prepared in Example 1 was weighed and added to a 300 μg / L mixed standard solution of 8 kinds of polychlorinated biphenyls (PCB28, PCB52, PCB101, PCB118, PCB153, PCB138, PCB180, PCB198) prepared in 10 mL of water-acetone (volume ratio 95:5). After mixing, the mixture was placed under constant temperature oscillation (100 r / min, 25° C.) for adsorption for a certain period of time. A magnet was used for solid-liquid separation. The solution was then transferred to a centrifuge tube, 5 mL of n-hexane was added, and the mixture was vortexed for 2 min. The concentration of polychlorinated biphenyls in the n-hexane layer was determined by gas chromatography. The concentration of polychlorinated biphenyls in the solution after adsorption equilibrium was calculated, and the adsorption amount Q of the adsorbent on polychlorinated biphenyls was calculated according to the following formula (1). The kinetic curves were fitted using pseudo-first-order kinetic model and pseudo-second-order kinetic model.
[0064]
[0065] Where: c0 and c e are the initial concentration and the concentration of PCBs after adsorption equilibrium, v and m are the volume of adsorption solution and the mass of adsorbent, respectively.
[0066] Figure 3The effect of adsorption time on the adsorption of polychlorinated biphenyls by magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer was studied. The results showed that the adsorption amount of 8 polychlorinated biphenyls increased significantly with the increase of adsorption time from 0 to 5 min. After more than 5 min, the adsorption amount did not change significantly, and the adsorption process reached a state of equilibrium. The adsorption process conformed to the pseudo-second-order kinetic model, indicating that the adsorption process was mainly chemical adsorption. The saturated adsorption amounts of PCB28, PCB52, PCB101, PCB118, PCB153, PCB138, PCB180 and PCB198 were calculated by fitting the pseudo-second-order kinetic model to obtain 98.04, 81.97, 77.04, 84.39, 91.74, 83.26, 83.40 and 96.99 μg / g, respectively. The above results show that the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer adsorbent has a strong adsorption effect and a high adsorption capacity for polychlorinated biphenyls.
[0067] 4. Study on static adsorption performance
[0068] 30 mg of the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer adsorbent prepared in Example 1 was weighed and added to a mixed standard solution of 8 kinds of polychlorinated biphenyls (PCB28, PCB52, PCB101, PCB118, PCB153, PCB138, PCB180, PCB198) of different concentrations prepared in 10 mL of water-acetone (volume ratio 95:5). After mixing, the mixture was adsorbed for 5 min at 25°C and 100 r / min. A magnet was used for solid-liquid separation. Then, the solution was transferred to a centrifuge tube, 5 mL of n-hexane was added, and vortexed for 2 min. The concentration of polychlorinated biphenyls in the upper n-hexane was determined by gas chromatography, and the equilibrium concentration in the solution after adsorption was calculated, and then the adsorption amount of polychlorinated biphenyls by the adsorbent was calculated. The adsorption isotherms were fitted by Langmuir and Freundlich models.
[0069] The results showed that the correlation coefficients of the Freundlich model fitting curves of the eight PCBs were higher than those of the Langmuir model, indicating that the Freundlich model was more suitable for describing the adsorption process of this adsorbent, which was a multilayer adsorption and the adsorbent surface was non-uniform.
[0070] 5. Recyclability
[0071] Weigh 30 mg of the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer adsorbent prepared in Example 1 into a 300 μg / L mixed standard solution of 8 kinds of polychlorinated biphenyls prepared in 10 mL of water-acetone (volume ratio 95:5), mix well, adsorb for 5 minutes at 25°C and 100 r / min, and measure the adsorption capacity. Place the adsorbent after solid-liquid separation with a magnet in an acetone-n-hexane (volume ratio 1:1) solution to ultrasonically elute the target. Repeat twice. Wash with ethanol and water several times, vacuum dry at 60°C for 12 hours, collect and weigh. Repeat adsorption-elution several times.
[0072] The results showed that after repeated adsorption for 5 times, the adsorption loss of 8 PCBs was less than 20%, indicating that the adsorbent has good reusability.
[0073] Experimental Example 2
[0074] The magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer composite material prepared in Example 1 was subjected to an adsorption and removal test of 8 polychlorinated biphenyls in simulated water samples and soil.
[0075] 1. Sewage testing
[0076] Water samples were collected from the outlet of a sewage treatment station. 10 mL of the water sample was filtered through a 0.22 μm water filter membrane, 20 μL of 8 kinds of PCB mixed standard solutions with a concentration of 10 μg / mL were added, and vortexed evenly. Then 30 mg of the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer adsorbent prepared in Example 1 was added, and adsorbed at 25°C and 100 r / min for 5 min. A magnet was used for solid-liquid separation, and the solution was transferred to a centrifuge tube. 2 mL of n-hexane was added and vortexed for 2 min. The concentration of PCBs in the upper n-hexane was determined by gas chromatograph, and the removal rate of PCBs in the water sample by the adsorbent was calculated.
[0077] The results showed that the removal rates of the adsorbent for PCB28, PCB52, PCB101, PCB118, PCB153, PCB138, PCB180 and PCB198 were 97.2%, 93.8%, 91.6%, 94.1%, 95.3%, 95.9%, 93.4% and 96.3%, respectively, which indicates that this adsorbent can achieve simultaneous adsorption and removal of 8 types of PCBs in actual water samples.
[0078] 2. Contaminated soil detection
[0079] Soil near the sewage outlet of a garbage dismantling station was collected as a soil sample. After the soil was naturally dried, it was crushed and sieved (pore size 1mm) for later use. Weigh 10g of soil sample in a centrifuge tube, add 10mL of water and 20μL of 8 kinds of polychlorinated biphenyl mixed standard solutions with a concentration of 10μg / mL, vortex evenly, let it stand for 30min to ensure that the soil is fully moistened, add 20mL of n-hexane and vortex extract for 20min, centrifuge at 8000r / min for 5min, collect the supernatant; the residue was extracted with 20mL of n-hexane repeatedly once, and the supernatant was combined. The supernatant was concentrated to near dryness under nitrogen, 10mL of water-acetone (volume ratio 95:5) was added for redissolution, the solution was transferred to an iodine volume flask, 30mg of the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer adsorbent prepared in Example 1 was added, and the remaining steps were the same as the water sample adsorption process. Finally, the removal rate of polychlorinated biphenyls in the soil by the adsorbent was calculated.
[0080] The results showed that the removal rates of the adsorbent for PCB28, PCB52, PCB101, PCB118, PCB153, PCB138, PCB180 and PCB198 were 99.15%, 95.7%, 92.8%, 93.1%, 96.4%, 96.6%, 95.4% and 97.8%, respectively, indicating that the adsorbent has a good adsorption and removal effect on 8 PCBs in soil.
[0081] The adsorption materials obtained in Examples 2 to 3 were tested for adsorption of sewage and contaminated soil in the same manner, and the test results were:
[0082] Example 2: The removal rates of PCB28, PCB52, PCB101, PCB118, PCB153, PCB138, PCB180 and PCB198 in sewage by the adsorbent were 93.6%, 90.5%, 88.4%, 91.2%, 93.0%, 91.3%, 90.5% and 92.7%, respectively. The removal rates of PCB28, PCB52, PCB101, PCB118, PCB153, PCB138, PCB180 and PCB198 in contaminated soil by the adsorbent were 93.8%, 90.1%, 91.6%, 90.9%, 95.1%, 94.1%, 94.7% and 94.2%, respectively.
[0083] Example 3: The removal rates of PCB28, PCB52, PCB101, PCB118, PCB153, PCB138, PCB180 and PCB198 in sewage by the adsorbent were 94.6%, 91.6%, 89.9%, 92.8%, 93.1%, 94.0%, 91.9% and 95.2%, respectively. The removal rates of PCB28, PCB52, PCB101, PCB118, PCB153, PCB138, PCB180 and PCB198 in contaminated soil by the adsorbent were 95.1%, 94.3%, 92.6%, 91.9%, 94.7%, 93.8%, 95.0% and 96.8%, respectively.
[0084] The above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer for rapid adsorption of polychlorinated biphenyls, characterized in that: The following steps are involved: S1. The unsaturated polyester resin is mixed with potassium hydroxide after a first calcination, and then ground and calcined for a second time to obtain a porous carbon material; S2. The porous carbon material is mixed with deionized water and ultrasonically dispersed, and then ferrous chloride tetrahydrate and ferric chloride hexahydrate are added and stirred to dissolve; after dissolution, nitrogen oxygen removal, heating, pH adjustment, constant temperature reaction, cooling, solid-liquid separation, and washing are sequentially performed to obtain a magnetic porous carbon material; S3. After a first mixing of cyclodextrin, sodium borohydride and double distilled water, a magnetic porous carbon material is added for a second mixing; then epichlorohydrin is added dropwise and a first stirring reaction is carried out; after the reaction is completed, the pH is adjusted, and then a second stirring reaction is carried out; after the reaction is completed, paraffin oil and Span / Tween compound emulsifier are added, and a third stirring reaction is carried out; after the reaction is completed, a mixed solution of water and acetone is added, and then the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer is obtained by filtering, washing and drying.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the calcined unsaturated polyester resin to potassium hydroxide in S1 is 1-10:1-10.
3. The preparation method according to claim 1, characterized in that: In the S1, the first calcination temperature is 200-400° C., and the calcination time is 1-3 hours; the second calcination temperature is 600-1000° C., and the calcination time is 1-3 hours.
4. The preparation method according to claim 1, characterized in that: The volume mass ratio of the porous carbon material, double distilled water, ferrous chloride tetrahydrate and ferric chloride hexahydrate in S2 is 0.2-0.5 g: 150-500 mL: 1-8 g: 5-15 g.
5. The preparation method according to claim 1, characterized in that: The heating temperature in S2 is 50-90°C.
6. The preparation method according to claim 1, characterized in that: In S2, the pH value is adjusted to 9-13, and the pH adjusting agent is 25% ammonia water.
7. The preparation method according to claim 1, characterized in that: The volume mass ratio of cyclodextrin, sodium borohydride, double distilled water, magnetic porous carbon material, epichlorohydrin, paraffin oil, Span / Tween compound emulsifier, water and acetone in S3 is: 0.5-5g: 2-50mg: 15-30mL: 2-4g: 1-10mL: 30-80mL: 5-40mL: 10-20mL: 10-20mL.
8. The preparation method according to claim 1, characterized in that: The pH value in S3 is adjusted to 6-10, and the pH adjusting agent is 0.1 mol / L sodium hydroxide solution.
9. A magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer for rapid adsorption of polychlorinated biphenyls, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.
10. The use of the magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer according to claim 9 in adsorbing polychlorinated biphenyl pollutants, characterized in that: The magnetic porous carbon@cyclodextrin / epichlorohydrin copolymer adsorbs polychlorinated biphenyls in soil and water samples.
